Shear Block Test Performance of Melunak and Mengkulang - Jihan Abd Malek, Nor; Hassan, Rohana; Ibrahim, Azmi; Hasan Alhebshi, Mohammed (International Journal of Engineering and Technology, 2018)
This paper presented results of shear block test performance of tropical glued-laminated timber (glulam) from species of melunak and mengkulang. Glulam blocks were manufactured in accordance with MS758:2001. The shear block test for glue lines and the shear strength tests of melunak and mengkulang were conducted and evaluated in accordance with BS EN 14080:2013. Melunak and mengkulang produced average shear strength values of 10.62 N/mm2 and 8.19 N/mm2, respectively. In terms of wood and glue failure percentage, the results showed that melunak and mengkulang were mainly failed due to wood surface area and not due to the glue lamination in which both melunak and mengkulang showed a good bonding performance.Â